Virginia Woolf: Lesbian readings - Barrett, Eileen; Cramer, Patricia (New York University Press, 1997)
The last two decades have seen a resurgence of critical and popular attention to Virginia Woolf's life and work. Such traditional institutions as The New York Review of Books now pair her with William Shakespeare in promotional advertisements; her face is used to sell everything from Barnes & Noble books to Bass Ale. Virginia Woolf: Lesbian Readings represents the first book devoted to Woolf's lesbianism. Divided into two sections, Lesbian Intersections and Lesbian Readings of Woolf's Novels, these essays focus on how Woolf's private and public experience and knowledge of same-sex love influences her shorter fiction and novels. Lesbian Intersections includes personal narratives that trace the experience of reading Woolf through the 60s, 70s, 80s, and 90s. Lesbian Readings of Woolf's Novels provides lesbian interpretations of the individual novels, including Orlando, The Waves, and The Years. Breaking new ground in our understanding of the role Woolf's love for women plays in her major writing, these essays shift the emphasis of lesbian interpretations from Woolf's life to her work.
Keywords: approches et analyses; arts; discipline; europe; lesbianisme; littérature; royaume-uni; régions géographiques; études littéraires